Non-pharmacological intervention to reduce pain post-appendectomy: A rapid review of randomized controlled trial studies - Nurohmah, Indah Syaidah; Putri, Nabila Aulia; Azwadina, Aliffa; Nuraeni, Fauziah; Riskyani, Umy; Hayati, Amelia; Rusmana, Hera Prafitri; Merdekawati, Rahayu; Rahayu, Urip; Pebrianti, Sandra (The Journal of Palembang Nursing Studies, 2023)
Background: Appendicitis leads to post-appendectomy pain with significant physical and mental implications, necessitating non-pharmacological pain management approaches. Objective: This study aimed to determine which non-pharmacological interventions can effectively reduce postoperative pain following an appendectomy. Design: A rapid review study design was employed. Data Sources: The databases used were EBSCOhost-CINAHL and PubMed. The article search was conducted on March 14, 2022. Review Methods: The identified articles were described using PRISMA guidelines and sorted based on inclusion criteria. These criteria included patients with appendicitis aged 18-59 years who underwent appendectomy, non-pharmacological pain management interventions, studies utilizing the Randomized Controlled Trial (RCT) method, full-text articles available, English language, and articles published between 2012-2022. Studies involving pediatric and elderly appendectomy patients, as well as studies with insignificant results, were excluded.  Results: Four articles were analyzed, revealing four types of interventions: Foot and Hand Reflexology (Massage), Lavender Aromatherapy and Almond oil (Aromatherapy), Inhalation aromatherapy with sweet-scented geranium essential oil, and Acupressure Le7. These interventions were then classified into two categories: aromatherapy-based interventions and neurostimulation-based interventions. All interventions were found to significantly reduce pain in appendectomy patients. Conclusions: Non-pharmacological therapies, such as lavender and almond oil aromatherapy, sweet-scented geranium aromatherapy, foot and hand reflexology, and Le7 acupressure, have demonstrated positive effects in reducing long-term pain after an appendectomy.